Exploring the role of APRIL in autoimmunity: implications for therapeutic targeting in systemic lupus erythematosus, rheumatoid arthritis, and Sjögren’s syndrome - Anastasia V. Poznyak; Elena V. Gerasimova; Nikolay A. Orekhov; Amina Eldarovna Karimova; Maria Andreevna Vergun; Ksenia Olegovna Lapshina; Vasily N. Sukhorukov; Alexander N. Orekhov (Frontiers in Immunology, 2025)
Autoimmunity arises when the immune system erroneously attacks self-antigens, potentially resulting in organ dysfunction. This review focuses on the proliferation-inducing ligand, APRIL, and its critical role in regulating antibody-producing B cells. We explore the implications of APRIL in autoimmune diseases such as systemic lupus erythematosus, rheumatoid arthritis, and Sjögren’s syndrome. Emerging evidence indicates that APRIL may modulate autoimmune pathology and influence B cell survival, particularly through its interactions with receptors like B-cell maturation antigen (BCMA) and transmembrane activator and CAML interactor (TACI). We emphasize the contrasting roles of APRIL and BAFF in autoimmunity, highlighting the conflicting data regarding their contributions to disease progression and activity levels. Furthermore, we evaluate therapeutic strategies aimed at inhibiting APRIL and compare them with existing B-cell-targeted therapies, such as rituximab and belimumab. The potential benefits of specific APRIL antagonism are discussed, especially for patients with antibody-driven autoimmune disorders. This highlights the necessity for further research into APRIL-targeted therapies in clinical practice. Ultimately, this review seeks to provide a comprehensive overview of the current understanding of APRIL’s role in autoimmunity and outline future directions for targeting this ligand in the treatment of autoimmune diseases.